Characterization of glycoconjugates and sialic acid modification in the olfactory bulb of the Chinese fire‐bellied newt (Cynops orientalis). (18th December 2019) - Matsui, Toshiyasu; Komamoto, Kazuyuki; Igarashi, Hitomi; Kurohmaru, Masamichi
Abstract: Diverse glycoconjugates are expressed in the vertebrate olfactory bulb and serve as guidance cues for axons of nasal receptor neurons. Although the involvement of glycoconjugates in the segregation of the olfactory pathway has been suggested, it is poorly understood in salamanders. In this study, lectin histochemistry was used to determine glycoconjugate distribution in the olfactory bulb of the Chinese fire‐bellied newt (Cynops orientalis) . Succinylated wheat germ agglutinin (sWGA), Ricinus communis agglutinin‐I and Lens culinaris agglutinin showed different bindings in the nerve fibre layer or glomerular layer, or both, between the main and accessory olfactory bulbs. We then investigated the lectin‐binding pattern after the removal of terminal sialic acids using neuraminidase. Desialylation resulted in a change in the binding reactivities with seven lectins. Wheat germ agglutinin, sWGA, soybean agglutinin (SBA) and peanut agglutinin showed different degrees of binding between the main and accessory olfactory bulbs. In addition, SBA showed a heterogeneous labelling of glomeruli in the rostral region of the main olfactory bulb. Our results suggest that terminal sialic acids mask the heterogeneity of glycoconjugates in the olfactory bulb of C. orientalis .